Highly organised direct farmers market: analysis of forms, characteristics, operations and women involvement in Japan (2007)
This study was based on the primary information collected from women farmers and coordinators of selected direct farmers markets in Sera and Ohnan Chuo, Hiroshima and Shimane prefecture respectively in Japan. Stratified and purposive sampling techniques were used to select respondents and direct farmers markets Information from direct farmers market coordinators and women farmers/processors was collected through interview schedule and structured questionnaires respectively. The study revealed that most of the direct farmers market studied were established for economic and social assistance of farmers. Requirements to participate varied from market to market. Low profit, competition and lack of sale were the major problems facing the respondents. Comparison of women farmers’ income from agriculture and non agriculture suggests better condition in agriculture than seeking employment outside the industry. Although, respondents were being empowered economically in some market and socially in others through participation in direct farmers market but both economics and social as well as political empowerment are essential for the market participants through involvement in the management activities of the market. Physically presence of farmers with their products on weekly, fortnightly or monthly basis should be initiated in order to build more social relationship among farmers and between farmers and consumers.